Archeologia o kulturze elitarnej wczesnośredniowiecznego Santoka. Wybrane zagadnienia - Kara, Michał (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2024)
The aim of this study is to present the results of an analysis of selected archaeological sources from early medieval functional-stratigraphic units discovered at site No. 1 in Santok (Poland, Lubusz Region), within are No. 297 (trench II). The finds come from archaeological excavations carried out between 1958 and 1961 of a multi-stage market settlement from the late 8th and 9th centuries, transformed into a fortified settlement in the late 9th or early 10th century. A comparative analysis of the individual sets of exclusive material culture has resulted in classifying the luxury objects discovered at Santok into several distinct macro groups of finds, differentiated in terms of chronology and cultural-spatial relationships. During the operation of the three oldest ‘open’ settlements in Santok (late 8th-2nd half of the 9th century), these relations were marked by contacts with the cultural population of the Feldberg-Bardy-Kędrzyno zone and with the artisanal and trading settlement at Menzlin (Germany, Mecklenburg NE). From the late 9th century onwards, contacts with Wolin started to prevail in Santok’s network of trans-regional links, evident in the material culture of Santok settlement No. IV. In the 10th century, it was probably extended to include relations with Szczecin. From the late 9th century onwards, in the elite culture of the Santok people relatively few exclusive objects marked their presence, typical of the culture of the Tornow-Klenica settlements, especially from the area of the middle Oder basin and the neighbouring Obra basin. On the other hand, finds from the relics of a younger castle stronghold in Santok – probably a Piast investment made after 970 on the remains of the so-called fortress No. 1 – document chronological and cultural similarities both with economically developed settlements in the Oder estuary region and with early Piast strongholds in central Wielkopolska (especially Poznań).